Etanercept treatment for pediatric toxic epidermal necrolysis induced by deflazacort: a case report and literature review - Jeong, Min Song; Choi, Yun Young; Ahn, Yo Han; Lee, Kyeonghun; Park, Ji Soo; Suh, Dong In (Frontiers in Immunology, 2024)
Toxic epidermal necrolysis (TEN) is a life-threatening mucocutaneous disorder commonly caused by drugs. TEN is often treated with corticosteroids, intravenous immunoglobulin (IVIG), or cyclosporine; however, the efficacy of these treatments is controversial. Etanercept (a TNF-α antagonist) was proven to decrease skin-healing time in a randomized clinical trial. Herein, we report the case of a 44-month-old boy who developed TEN due to deflazacort as the probable culprit drug and was successfully treated with etanercept. The patient presented to the emergency department complaining of erythematous maculopapular rashes and vesicles all over the face and body, with vesicles on the hands, feet, and trunk. Symptoms started 4 days before presentation, with edema of the upper lip, which progressed to erythematous macules over the body. He was started on deflazacort for nephrotic syndrome 21 days before the visit. Approximately 20% of the body surface area (BSA) was covered by vesicular lesions. Under the diagnosis of Steven Johnson syndrome/TEN, deflazacort was discontinued, and intravenous dexamethasone (1.5 mg/kg/day), a 5-day course of IVIG (0.4 mg/kg/day), and cyclosporine (3 mg/kg/day) were administered. The lesions seemed to be stationary for 3 days, but on the 6 th day of hospitalization, when IVIG was discontinued, the vesicular lesions progressed to approximately 60% of the BSA. Etanercept 0.8 mg/kg was administered subcutaneously. Lesions stopped progressing, and bullous lesions started epithelialization. However, on the 15th day, around 30% of the BSA was still involved; thus, a second dose of etanercept was administered. No acute or sub-acute complications were observed. In conclusion, the use of etanercept in children with TEN that is not controlled with conventional therapy is both effective and safe.